Peran Sertifikasi Halal Dalam Menjamin Keamanan Dan Kepatuhan Produk Bagi Konsumen Muslim - Mastawiyah; Dea Putri Ananda; Eliyani (Indo Publishing, 2026)
Halal certification has become a crucial instrument in ensuring product safety and compliance for Muslim consumers, given the growing public awareness of the halal nature of products in accordance with Sharia principles. The purpose of this study is to analyze the role of halal certification in protecting Muslim consumers, ensuring producer compliance with regulations, and increasing consumer trust in products. The research method used was descriptive qualitative, with a literature review approach based on regulations, national journals, and literature related to halal certification and Muslim consumer behavior. The results indicate that halal certification not only serves as a sign of legal compliance but also serves as moral and spiritual protection for Muslim consumers, helping them avoid products with questionable halal status (syubhat), and increasing consumer trust and loyalty. In conclusion, halal certification plays a dual role as a guarantee of product safety and a consumer protection instrument, while also supporting business actors in complying with regulations and maintaining their business reputation in accordance with the principles of faith.